The effect of some active compounds of the Aqueaus extract of Basil on some bloodhematological parameters of male rats induced with Diabetes - Noor Al-Huda N. Abdulla; Adnan S. Abdulnabi; abdulahseen, murtadha F. (University of Thi-Qar Journal of agricultural research, 2025)
Diabetes mellitus is one of the major scientific problems facing the human body due to its delayed detection at its onset. It is often referred to as the silent killer. Cardiovascular disease, renal disease, and neuropathy are among the many complications that can develop in people with diabetes. The pancreatic beta cells secrete the hormone insulin. Its regulation of metabolism is crucial for maintaining normal blood sugar levels. Due to the complications caused by chemotherapy and its high cost, medicinal herbs have been used in this field to reduce the effects of diabetes and lower blood levels. One such herb is basil. Its aqueous leaf extract is used to treat diabetes, given its content of active compounds such as flavonoids, alkaloids, saponins, and other compounds.Forty adult male albino rats were evaluated. They weighed between 200 and 250 grams and were 10 to 12 weeks old. Four groups were formed from them. A control group, which did not receive any therapy, was the first. On the other hand, 150 mg/kg bw of alloxan was administered to the second group. The third set of subjects received alloxan injections and a monthly dosage of 250 mg/kg bw of water-based basil leaves extract. The fourth set of subjects received a single alloxan injection, along with a monthly dosage of aqueous basil leaves extract (500 mg/kg body weight). Following the injection of alloxan, the findings demonstrated a significant decline (p < 0.05) in the quantity of red blood cells, compressed cell volume, and hemoglobin concentration. As shown in the control group, the levels increased once more after administering the aqueous basil leaf extract. Nevertheless, in contrast to the control group, the alloxan injection resulted in a substantial increase (p<0.05) in the number of white blood cells. It dropped down to levels similar to the control group after the administration of the water-based basil leaves extract (p<0.05).